EVOLUTION OF THE MARKETING PARADIGM: A NEW VISION - G. V. Astratova; O. A. Rushchitskaya (Russian Journal of Economics and Law)
Objective: to confirm the feasibility of using the disciplinary matrix by Th. Kuhn in relation to the marketing theory.Methods: paradigmatic and systemic methods of analysis of marketing phenomena.Results: to date, the paradigm as a specific tool of scientific research is poorly studied in the marketing methodology in contrast to other branches of knowledge. An analysis of available literature revealed no sources that use the famous disciplinary matrix by Th. Kuhn and its components: symbolic generalizations, metaphysical parts, values and conventional samples - in relation to marketing.The content of the marketing paradigm is described as the disciplinary matrix by Th. Kuhn, which was composed of the four above-mentioned elements: 1) symbolic generalizations are the expressions that are used by members of the scientific community without disagreements and doubts and can be easily formalized or verbalized (e.g., definition of marketing); 2) metaphysical parts of modern marketing are a set of the existing concepts and theories (e.g., theory of stages of marketing evolution); 3) values in the context of the marketing paradigms are considered by the authors through emphasis on three research objects: a) goods (service) - creation of new goods and/or formation of a set of qualities inherent in the goods (service), perceived by the consumer as a combination of rational and emotional values of the product; b) customer - development of "value proposition for the consumer"; c) seller/manufacturer - basing on the concept of "value chain" that builds strategic management of the company; 4) conventional samples of the marketing paradigm include standards, or algorithms, models and methods of solving specific problems of marketing research (for example, a diagram of the stages of the marketing research process and industrial standards of their conduct). Scientific novelty: the appropriateness of the disciplinary matrix by Th. Kuhn in relation to the marketing theory was confirmed.Practical significance: the main provisions and conclusions of the article can be used in research and teaching, in considering the conceptual issues of the evolution of the notion and essence of marketing as a system of scientific knowledge. The identified quality content of each element of the matrix with regard to marketing paradigm can be a motivating starting point for further quantitative studies of the content of the disciplinary matrix.